Competitiveness of the Wielkopolska region in terms of a knowledge-based economy - Czyż, Teresa (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2010)
In the study of the competitiveness of the Wielkopolska region it is assumed that in modern times the foundation of a competitive advantage is a knowledge-based economy (KBE). The aim of the article is to analyse the competitiveness of the Wielkopolska region (voivodeship) in terms of KBE in comparison with the country’s regional system. Four dimensions of the region’s competitiveness are distinguished, representing factors of KBE development and effects of their operation in the economic sphere. With the help of principal components analysis, indices of the region’s competitiveness are obtained.
Keywords: knowledge-based economy; region’s competitiveness; dimensions of competitiveness; principal components analysis; Wielkopolska region